PENGARUH LIKUIDITAS, STRUKTUR AKTIVA, KEPEMILIKAN MANAJERIAL, TINGKAT PERTUMBUHAN TERHADAP STRUKTUR MODAL - Wibisono, Muhammad Irsyad Rasyid; Murtanto (Jurnal Ekonomi Trisakti, 2026)
This study aims to analyze the effect of liquidity, asset structure, managerial ownership, and sales growth rate on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach with secondary data obtained from company financial reports. The research sample was determined using purposive sampling and analyzed with multiple linear regression using the EViews program. Capital structure is proxied by the Debt to Equity Ratio (DER), while the independent variables include liquidity proxied by the Current Ratio (CR), asset structure proxied by the Fixed Asset Ratio (FAR), managerial ownership, and sales growth rate. The results show that liquidity has a positive and significant effect on capital structure, while asset structure has a negative and significant effect on capital structure. Meanwhile, managerial ownership and sales growth rate do not have a significant effect on capital structure. These findings indicate that corporate capital structure decisions are more influenced by internal financial conditions, particularly liquidity and asset composition, than by managerial ownership and sales growth. This study is expected to contribute to corporate management and investors in making optimal financing decisions.